Pelaksanaan Pembelajaran Muatan Lokal Bahasa Inggris di SD Negeri 25 Kota Bengkulu - Rahma Mutiara; Syahril Yusuf; Lukman Lukman (Universitas Bengkulu, 2019)
This study aims to describe the planning, implementation, and assessment english language of local content learning in SD Negeri 25 Kota Bengkulu. This research is a descriptive research with qualitative research type. The subjects of this study were English teachers and students. Data collection techniques use observation, interviews, and documentation. Test the credibility of data through increased persistence and triangulation. The data that have been obtained is analyzed by data reduction, data presentation, and conclusion. The results of this study are (1) at the planning stage has been done by making syllabus and rpp; (2) at the implementation stage the teacher has carried out the three stages of the learning process ie preliminary activities, core activities, and closing activities; (3) at the assessment stage the teacher has carried out the assessment of aspects of knowledge and attitude. Based on the results of the research can be concluded that the teacher has carried out the planning, implementation, and assessment. However, there are several components that need to be improved, such as developing affective and psychomotor indicators.